Waste reduction in plastic bottle manufacturing for drinking water industry - Itthiprom, Radamanee; Dutchanee, Somruetai; Saikaew, Charnnarong (Engineering and Applied Science Research, 2014)
The purpose of this study was to improve the quality of plastic water bottle by focusing on reducing the amount of waste. This study began with the determination of symptoms and causes of the problem by analyzing types and amount of waste with 7 quality control tools (7 QC tools). The results from 7 QC tool analysis showed that one of the most important symptoms of the problem was bottle scratching caused by bubble in plastic pre-form tube after receiving from the injection molding process. The technique of 2k factorial design was used to study the effects of three process factors (i.e., temperature at the three machines in the drying process of plastic pellets) on the amount of waste. The results showed that temperatures were significant and the optimal operating conditions of the significant factors were at the high level of each of the temperature. Moreover, at the optimal operating conditions, waste of bottle scratching was reduced from 0.248% to 0.18%.